Hungary: Between Democracy and Authoritarianism - EM Saltman (Slovo, 2012)
Saltman, EM (2012) Hungary: Between Democracy and Authoritarianism. By PAUL LENDVAI. Pp. 288. New York: Columbia University Press. 2012. $35. Cloth. ISBN: 978-0-231- 70322-2. [Review]. Slovo , 24 (2). Click here to read the review.